2020
DOI: 10.3390/molecules25020424
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Photochemistry of European Mid-Latitudes Rivers: An Assessment of Their Ability to Photodegrade Contaminants

Abstract: The abiotic photochemical reactions that take place naturally in sunlit surface waters can degrade many contaminants that pose concern to water bodies for their potentially toxic and long-term effects. This works aims at assessing the ability of European rivers to photoproduce reactive transient intermediates, such as HO• radicals and the excited triplet states of chromophoric dissolved organic matter (3CDOM*), involved in pollutant degradation. A photochemical mapping of the steady-state concentrations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Thus, models are often used to predict the photochemical lifetimes of pollutants. For example, Carena and Vione conducted modeling work and map the formation of PPRIs in European mid-latitudes rivers to gain insight into the photodegradation kinetics of water pollutants. Zeng and Arnold investigated the photodegradation of pesticides in surface waters and estimated the second-order rate constants for their reactions with PPRIs .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, models are often used to predict the photochemical lifetimes of pollutants. For example, Carena and Vione conducted modeling work and map the formation of PPRIs in European mid-latitudes rivers to gain insight into the photodegradation kinetics of water pollutants. Zeng and Arnold investigated the photodegradation of pesticides in surface waters and estimated the second-order rate constants for their reactions with PPRIs .…”
Section: Resultsmentioning
confidence: 99%
“…Details about the modeling procedure are reported in Text S2. It was considered a reasonable 2 m deep water column, while DOC ranged from <1 to ∼10 mg C L –1 (nitrate and nitrite were not included in the model, because such data are lacking, which might slightly underestimate photoreaction kinetics) . It is suggested that IBAP volatilization from surface-water environments to the gas phase is potentially quite significant as it may approach up to 25% for the considered scenarios.…”
Section: Environmental Significancementioning
confidence: 99%
“…This method could also open up the way to the definition of environmental vulnerability, in the context of photochemical reactions. 4 Currently, photoreaction pathways are well-known for only a small selection of contaminants. Moreover, the characterization and quantification of the formation yields of intermediates faces several challenges, which include the following:…”
mentioning
confidence: 99%
“…Maps of the formation yields in sunlit river water of (left) 10,11-dihydro-10,11-trans-dihydroxycarbamazepine from carbamazepine, and (right) 4-chlorophenol from clofibric acid. The calculation procedure is described in previous work . Many sites of central-southern France have the highest potential to produce the former intermediate, and the lowest potential to produce the latter.…”
mentioning
confidence: 99%
See 1 more Smart Citation